Pengaruh Pengetahuan dan Sikap Terhadap Kepatuhan Minum Obat Pada Penderita TB Paru - Ardat Ardat (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
One type of generative disease that has been infected for a long time amid Indonesian society, which attacks the productive age group and children and is the number one killer infectious disease. Non-compliance with taking the medication regularly for TB sufferers can hinder the achievement of cure rates. The magnitude and extent of the problems caused by pulmonary TB require all parties to be able to commit and cooperate in the prevention of pulmonary TB. The purpose of this study is to determine the influence of knowledge and attitudes towards adherence to taking medication. The research design is a Cross-Sectional Study with an observational approach. The sample in this study were 39 people with pulmonary TB data collection instruments using a questionnaire. Data analysis with Che-Square analysis. The results of the study found that knowledge and attitudes had an effect on the value of p = 0,0001 and attitude had an effect on the value of p = 0.004. The conclusion of adherence is strongly influenced by the behavior and habits of one of them is knowledge